A scaling analysis for electrohydrodynamic convection with variable thermophysical and electrical properties. (June 2017) - Kunti, Golak; Bhattacharya, Anandaroop; Chakraborty, Suman
Graphical abstract: Highlights: Scaling analysis of EHD convective transport is presented. Scaling relationships for the Nusselt number as a function of the relevant electrical Rayleigh numbers are presented. Corroboration between numerical simulations and the scaling theory. Temperature dependent thermo-physical and electrical properties are considered to improve the numerical results. Abstract: Electrohydrodynamic (EHD) effects cause fluid motion when an external electric field is imposed on a dielectric fluid medium. In this work, a detailed scaling analysis of EHD convective transport is presented, taking into account the interplay of electrophoretic, dielectrophoretic, and electrostriction forces and the variable nature of the concerned thermophysical and electrical properties. Our results bring out the scaling relationships for the Nusselt number as a function of the relevant electrical Rayleigh number ( Ra EL 1 and Ra EL 2 ), for different operating regimes, and provide important insights into the relative dominances of the different forces. The Nusselt number is found to scale with Ra EL 1 0.25 when the Coulomb force dominates, and with Ra EL 2 0.333 when electrostriction force dominates. Numerical simulations are also conducted for some representative test cases and the results are found to corroborate the scaling theory.